2019
DOI: 10.1093/ntr/ntz046
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Self-reported Practices of Health Care Professionals Regarding Electronic Nicotine Delivery Systems: A Mixed-Methods Systematic Review and Synthesis

Abstract: Aims This review explores the (1) beliefs and attitudes of health care professionals (HCPs) toward electronic nicotine delivery systems (ENDS) including use as a smoking cessation aid and/or harm reduction, safety and regulation, and (2) the extent and content of patient–HCP communication about ENDS. Methods PubMed, Embase, CINAHL, and PsycINFO were searched to identify articles published since 2003. The Mixed Methods Apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 71 publications
6
31
0
Order By: Relevance
“…However, information sourced from the media and/or anecdotal experiences may be biased and could lead to confusion as the content may not be scientifically valid. The finding that few participants had received advice from a health-care professional about NVPs corroborates findings from a recent systematic review, which found health-care professionals do not engage in routine communication with patients regarding NVPs and other low risk alternatives to smoking [18]. Due to their geographic distribution and ease of accessibility, community pharmacies represent an ideal setting to educate the public and promote behaviours that improve health, one of which is smoking cessation.…”
Section: Discussionsupporting
confidence: 79%
“…However, information sourced from the media and/or anecdotal experiences may be biased and could lead to confusion as the content may not be scientifically valid. The finding that few participants had received advice from a health-care professional about NVPs corroborates findings from a recent systematic review, which found health-care professionals do not engage in routine communication with patients regarding NVPs and other low risk alternatives to smoking [18]. Due to their geographic distribution and ease of accessibility, community pharmacies represent an ideal setting to educate the public and promote behaviours that improve health, one of which is smoking cessation.…”
Section: Discussionsupporting
confidence: 79%
“…The majority of respondents in our study do not recommend or would not recommend ECs to their patients for smoking cessation or reducing the number of cigarettes smoked, consistent with other studies 8,9 and aligned with current recommendations in Slovenia. However, responses of those recommending ECs in other studies substantially differ, from none to a third or more 7,9,[18][19][20][22][23][24] .…”
Section: Discussionsupporting
confidence: 88%
“…In our study we found a notable difference in the range from around 6% to 13% and 14%. They would mostly recommend ECs in case of patients' queries and less likely proactively, as shown in other studies 8 . Other studies have shown that patient interest may be a significant promoter for a healthcare professional's recommendation 25 .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations